Evaluation of metallic brackets adhesion after the use of bleaching gels with and without amorphous calcium phosphate (ACP): in vitro study - Sissy Maria Mendes Machado; Diego Bruno Pinho do Nascimento; Robson Costa Silva; Sandro Cordeiro Loretto; David Normando (Dental Press Editora, 2013)
OBJECTIVE: To evaluate in vitro the effects of tooth whitening using gel with Amorphous Calcium Phosphate (ACP) on the bond strength of metal brackets. METHODS: Thirty-six bovine incisors were sectioned at the crown-root interface, and the crowns were then placed in PVC cylinders. The specimens were divided into 3 groups (n = 12) according to whitening treatment and type of gel used, as follows: G1 (control) = no whitening; G2 = whitening with gel not containing ACP (Whiteness Perfect - FGM), G3 = whitening with gel containing ACP (Nite White ACP - Discus Dental). Groups G2 and G3 were subjected to 14 cycles of whitening followed by an interval of 15 days before the bonding of metal brackets. Shear bond strength testing was performed on a Kratos universal test machine at a speed of 0.5 mm/min. After the mechanical test, the specimens were assessed to determine the adhesive remnant index (ARI). The results were subjected to ANOVA, Tukey's test and Kruskal-Wallis test (5%). RESULTS: Significant differences were noted between the groups. Control group (G1 = 11.10 MPa) showed a statistically higher shear bond strength than the groups that underwent whitening (G2 = 5.40 Mpa, G3 = 3.73 MPa), which did not differ from each other. There were no significant differences between the groups in terms of ARI. CONCLUSION: Tooth whitening reduces the bond strength of metal brackets, whereas the presence of ACP in the whitening gel has no bearing on the results.